Genotype-Phenotype Characterization of Wolf-Hirschhorn Syndrome Confirmed by FISH: Case Reports. (22nd November 2012) - Sheth, F.; Akinde, O. R.; Datar, C.; Adeteye, O. V.; Sheth, J.
Abstract : The Wolf-Hirschhorn syndrome (WHS) is a multiple malformation and contiguous gene syndrome resulting from the deletion encompassing a 4p16.3 region. A microscopically visible terminal deletion on chromosome 4p (4p16→ pter) was detected in Case 1 with full blown features of WHS. The second case which had an interstitial microdeletion encompassing WHSC 1 and WHSC 2 genes at 4p16.3 presented with less striking clinical features of WHS and had an apparently "normal" karyotype. The severity of the clinical presentation was as a result of haploinsufficiency and interaction with surrounding genes as well as mutations in modifier genes located outside the WHSCR regions. The study emphasized that an individual with a strong clinical suspicion of chromosomal abnormality and a normal conventional cytogenetic study should be further investigated using molecular cytogenetic techniques such as fluorescence in situ hybridization (FISH) or array-comparative genomic hybridization (a-CGH).